In Vivo Functional Selection Identifies Cardiotrophin-1 as a Cardiac Engraftment Factor for Mesenchymal Stromal Cells. Issue 16 (17th October 2017) - Bortolotti, Francesca; Ruozi, Giulia; Falcione, Antonella; Doimo, Sara; Dal Ferro, Matteo; Lesizza, Pierluigi; Zentilin, Lorena; Banks, Lawrence; Zacchigna, Serena; Giacca, Mauro
Abstract : Background: Transplantation of cells into the infarcted heart has significant potential to improve myocardial recovery; however, low efficacy of cell engraftment still limits therapeutic benefit. Here, we describe a method for the unbiased, in vivo selection of cytokines that improve mesenchymal stromal cell engraftment into the heart both in normal conditions and after myocardial infarction. Methods: An arrayed library of 80 secreted factors, including most of the currently known interleukins and chemokines, were individually cloned into adeno-associated viral vectors. Pools from this library were then used for the batch transduction of bone marrow–derived mesenchymal stromal cells ex vivo, followed by intramyocardial cell administration in normal and infarcted mice. Three weeks after injection, vector genomes were recovered from the few persisting cells and identified by sequencing DNA barcodes uniquely labeling each of the tested cytokines. Results: The most effective molecule identified by this competitive engraftment screening was cardiotrophin-1, a member of the interleukin-6 family. Intracardiac injection of mesenchymal stromal cells transiently preconditioned with cardiotrophin-1 preserved cardiac function and reduced infarct size, parallel to the persistence of the transplanted cells in the healing hearts for at least 2 months after injection. Engraftment of cardiotrophin-1–treated mesenchymal stromal cells was consequent to signal transducer and activator of transcription 3–mediated activation of the focal adhesion kinase and its associated focal adhesion complex and the consequent acquisition of adhesive properties by the cells. Conclusions: These results support the feasibility of selecting molecules in vivo for their functional properties with adeno-associated viral vector libraries and identify cardiotrophin-1 as a powerful cytokine promoting cell engraftment and thus improving cell therapy of the infarcted myocardium. Abstract : Supplemental Digital Content is available in the text.